2021
DOI: 10.1016/j.jse.2020.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic and kinematic study of reverse total shoulder arthroplasty: an observational prospective cohort study

Abstract: Background: Reverse total shoulder arthroplasty (RTSA) procedures have significantly increased in the last decade as an alternative to the current treatments for cuff-tear arthropathy. Since Grammont's theory in 1987, few data about the in vivo kinetics of the shouldergirdle musculature in patients with RTSA have been available. The goals of this study are to (1) describe the contribution of principal muscles around the shoulder by electromyography and (2) access the range of motion of 5 movements of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…According to the electromyographic result reported by Pelletier-Roy et al, 23) RTSA intervenes in cuff-defect shoulders by modifying the scapulothoracic sequence. Further lengthening of the distance between the medial border of the scapula and the glenohumeral joint by lateralization not only affects the tension of rotators, but also the scapulothoracic muscles, especially the upper trapezius and latissimus dorsi, which are known to be the main activator muscles in RTSA shoulders.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the electromyographic result reported by Pelletier-Roy et al, 23) RTSA intervenes in cuff-defect shoulders by modifying the scapulothoracic sequence. Further lengthening of the distance between the medial border of the scapula and the glenohumeral joint by lateralization not only affects the tension of rotators, but also the scapulothoracic muscles, especially the upper trapezius and latissimus dorsi, which are known to be the main activator muscles in RTSA shoulders.…”
Section: Discussionmentioning
confidence: 98%
“…Further lengthening of the distance between the medial border of the scapula and the glenohumeral joint by lateralization not only affects the tension of rotators, but also the scapulothoracic muscles, especially the upper trapezius and latissimus dorsi, which are known to be the main activator muscles in RTSA shoulders. 23) However, this theory only can be applied in the setting of implants with increased offset on the glenoid side. So far, numerous clinical studies have compared two or three different products that represent either medialized or lateralized RTSA systems.…”
Section: Discussionmentioning
confidence: 99%
“…In our view, scapulothoracic motion, which is differentiated by lateralization, might affect the ER gain. Using electromyography, Pelletier-Roy et al 23 demonstrated that shoulder motion intervention using rTSA was affected by modified scapulothoracic sequencing. They reported that the upper trapezius and latissimus dorsi are the main activator muscles in the rTSA shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle activity or adaptation can be assessed through muscle tests, invasively using small needle electrodes, or with surface electrodes adhered to the skin. Surface electromyography (sEMG) has recently shown to be a valid and noninvasive tool for quantifying individual muscle activation in the shoulder and has been used extensively in clinical diagnostic and rehabilitation settings [3,[6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%